The Value of Measurements, in Desgodets and Palladio (diségno, 2020)
In 1682, Antoine Desgodets published Les édifices antiques de Roma dessinés et mesurés très exactement, confirming the imprecision of the data published by the Italian architects of the previous century, singularly by Palladio in his Quarto libro dell’architettura, whose errors he does not cease to denounce in his book. This is a question that raises the confrontation of two attitudes in the face of the knowledge of antiquity that refers to the very objective of architectural representation. Between the indisputable value of data and the ambiguity of intuitive knowledge. Between Desgodets’s drawings, of unquestionable quality, but limited to what he can verify, and Palladio’s compositions, of an almost radical abstraction, capable of incorporating what Raphael understood as “seeing as painters”, without renouncing the orthogonal drawing of plant, section and elevation.